Strengthening the Character of Responsibility in 5-6 Year Old Children through Class Agreements - Intan Nur Aini; Mursid Mursid; Naila Fikria Afrih Lia (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
The topic of strengthening the character of responsibility in early childhood is important because this skill forms the foundation of self-regulation, which supports children’s social competence and lifelong learning. This study aims to describe the process of strengthening the character of responsibility in 5–6-year-old children through the implementation of class agreements during play activities. The research used a descriptive qualitative approach with instruments including participant observation, in-depth interviews with the teacher, and documentation of learning activities, involving children in group B as research subjects and the class teacher as the main informant. Data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing to understand the practice of class agreements in context. The results indicate that class agreements were developed collaboratively through open discussions between the teacher and children and were consistently applied during play, fostering responsibility evidenced by children’s ability to tidy play tools, maintain cleanliness, help peers, and recognize the consequences of their actions. The practical implications suggest the importance of participatory child involvement in creating class rules to build early self-regulation and recommend further research across other educational levels or with more intensive parental involvement.